FROM MINISTER TO PRESIDENT: MEARSHEIMERISM IN INDONESIA'S DEFENSE DIPLOMACY UNDER PRABOWO SUBIANTO ADMINISTRATION - Renaldo Benarrivo (Universitas Jenderal Ahmad Yani, 2024)
The invitation of John Mearsheimer as a geopolitical speaker at the ministerial candidates briefing event entitled “Hambalang Retreat” by President Prabowo Subianto on October 17, 2024, illustrates the president's particular preferences regarding geopolitical topics that are heavily influenced by thoughts of Mearsheimer that in this article are referred to as “Mearsheimerism”. This has been reflected since the beginning of Subianto’s leadership in the Indonesian Ministry of Defense, which is attractive to review regarding the extent to which the contextualization of structural realism has been in defense policy decision-making, especially in Indonesia's defense diplomacy. Explaining how the government carried out its defense diplomacy process under the Subianto administration is necessary and exciting. This research was conducted using the qualitative research method. The results found several linearities between the main ideas of Mearsheimer and the main ideas of Indonesia's defense diplomacy.